2019
DOI: 10.1126/science.aau5870
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces rapid changes to histone methylation and reprograms chromatin

Abstract: Oxygen is essential for the life of most multicellular organisms. Cells possess enzymes called molecular dioxygenases that depend on oxygen for activity. A subclass of molecular dioxygenases is the histone demethylase enzymes, which are characterized by the presence of a Jumanji-C (JmjC) domain. Hypoxia can alter chromatin, but whether this is a direct effect on JmjC-histone demethylases or due to other mechanisms is unknown. Here, we report that hypoxia induces a rapid and hypoxia-inducible factor–independent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
240
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(256 citation statements)
references
References 50 publications
15
240
1
Order By: Relevance
“…Alternatively, cellular oxygen sensing could be coupled to gene expression through chromatin states in an HIF1A-independent manner. Independent studies recently discovered direct oxygen sensing by KDM6A/UTX (the H3K27 demethylase lost in KS2 patients) as well as the H3K4/H3K36 demethylase 5A (KDM5A), which controlled chromatin states and cell differentiation in an HIF1A-independent manner (36,37). These findings link hypoxia-induced histone methylation at H3K4, H3K27, H3K9, and H3K36 directly with control of maturation in multiple cell types, further supporting the notion that KS-associated transcriptional suppression, in the adult DG context, could affect NSPC stage-dependent learning (34) via metabolic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, cellular oxygen sensing could be coupled to gene expression through chromatin states in an HIF1A-independent manner. Independent studies recently discovered direct oxygen sensing by KDM6A/UTX (the H3K27 demethylase lost in KS2 patients) as well as the H3K4/H3K36 demethylase 5A (KDM5A), which controlled chromatin states and cell differentiation in an HIF1A-independent manner (36,37). These findings link hypoxia-induced histone methylation at H3K4, H3K27, H3K9, and H3K36 directly with control of maturation in multiple cell types, further supporting the notion that KS-associated transcriptional suppression, in the adult DG context, could affect NSPC stage-dependent learning (34) via metabolic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that chromatin contacts exist between HIF1α binding sites and hypoxiainducible genes in the normoxic state (Platt et al, 2016). Conversely, it has been suggested that hypoxia results in the induction of HIF1α, and significant changes in histone methylation (Batie et al, 2019). As we did not measure histone marks in our system, these changes may occur in the absence of chromatin accessibility changes, but we also cannot rule out the possibility that the choice of a single timepoint following six hours of hypoxia, or insufficient statistical power in our sample size, contributed to the minimal differences in accessibility that we observed.…”
Section: Mechanisms Behind Response Genes and Dynamic Eqtlsmentioning
confidence: 99%
“…The heart is a complex tissue consisting of multiple cell types, yet the bulk of the volume of the heart is comprised of cardiomyocytes Pinto et al, 2016), which are particularly susceptible to oxygen deprivation given their high metabolic activity. iPSC-derived cardiomyocytes (iPSC-CMs) have been shown to be a useful model for studying genetic effects on various cardiovascular traits and diseases, as well for studying gene regulation (Banovich et al, 2018;Benaglio et al, 2019;Brodehl et al, 2019;Burridge et al, 2016;de la Roche et al, 2019;Ma et al, 2018;McDermott-Roe et al, 2019;Panopoulos et al, 2017;Pavlovic et al, 2018;Ward and Gilad, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Histone markers associated with active transcription were globally decreased within the DNA following synthetic androgen R1881 treatment. In contrast hypoxia marginally increased the presence the two histone markers, it has previously been reported that hypoxia rapidly increases histone methylation independently of HIF [33]. Despite decreasing the prevalence of H3K4me3, the location of the histone marker within promoter regions was increased as a result of R1881 treatment and indicates enhanced transcriptional activity.…”
Section: Discussionmentioning
confidence: 90%